2021
DOI: 10.18261/issn.2464-3076-2021-02-02
|View full text |Cite
|
Sign up to set email alerts
|

«Kan vi hjelpe når krisa rammer?»Barnevern, smittevern og store forskjeller i tjenestene under covid-19-pandemien

Abstract: Vitenskapelig publikasjon «Kan vi hjelpe når krisa rammer?» Barnevern, smittevern og store forskjeller i tjenestene under covid-19-pandemien 'When crisis strikes, can we help?' Child welfare, infection control and substantial variances in services during the Covid-19 pandemic Vibeke Krane Førsteamanuensis og faggruppeleder, Senter for psykisk helse og rus, Institutt for helse-, sosial-og velferdsfag,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Our participants’ description of VC as ‘not real therapy’ resembles findings of therapists’ descriptions of VC as ‘a filter for emotions’ [ 6 ]. Other studies have also pointed out that subtle cues, facial expressions and body language that might be essential for showing empathy, genuineness and engagement could be lost in virtual communication [ 9 , 26 ]. Moeller’s [ 46 ] review of adults’ experiences of VC is in line with this finding: all of the included studies found that patients mentioned that VC contact with the therapist was less personal and intense than in person.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our participants’ description of VC as ‘not real therapy’ resembles findings of therapists’ descriptions of VC as ‘a filter for emotions’ [ 6 ]. Other studies have also pointed out that subtle cues, facial expressions and body language that might be essential for showing empathy, genuineness and engagement could be lost in virtual communication [ 9 , 26 ]. Moeller’s [ 46 ] review of adults’ experiences of VC is in line with this finding: all of the included studies found that patients mentioned that VC contact with the therapist was less personal and intense than in person.…”
Section: Discussionmentioning
confidence: 99%
“…However, structural inequality in access to technological solutions and disparities in knowledge of digital tools have been highlighted [9,21,24,25]. Digital solutions in CAMHS and CWS also pose confidentiality and safety risks as clients need a stable internet connection and privacy for a VC [20,22,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations